Lightning impulse strength of 275 kV and 132 kV tower with composite crossarm - Abd Rahman M.S.; Ab Kadir M.Z.A.; Ab-Rahman M.S.; Osman M.; Nor S.F.M. (Institute of Electrical and Electronics Engineers Inc., 2023)
Electric insulation; Electric power transmission; Flashover; Towers; ANSYS Maxwell; Electric field profiles; Feasibility studies; Lightning activity; Lightning over-voltage; Lightning performance; Lightning strikes; Transmission tower; Lightning